2007
DOI: 10.1108/13563280710744801
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of supervisor communication on organizational commitment

Abstract: PurposeIn an attempt to gain insight in the contribution of organizational communication to work perceptions, this paper investigates both direct and indirect relationships between supervisor communication and employees' affective organizational commitment. Regarding the indirect relationships, individual perceptions of person‐organization fit and organizational efficacy were included in the model as mediators.Design/methodology/approachA survey from a Dutch provider of telecommunication services (n=456) is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 48 publications
4
66
0
2
Order By: Relevance
“…de Ridder (2004)in his study of 791 employees from various organization in the Netherlands demonstrated that communication produces greater employee commitment. According to Van Vuuren, De Jong, and Seydel (2007),when an organization makes an attempt to provide sufficient information to its employees regarding the organization's vision, goals, and strategies, employees will feel that they are being valued, respected, and trusted by the organization. Furthermore, Van Vuuren et al (2007) advocated that communication helps sharpen employees' view of the things that the organization cherishes.…”
Section: Identification With Organizational Values and Goals As A Medmentioning
confidence: 99%
See 1 more Smart Citation
“…de Ridder (2004)in his study of 791 employees from various organization in the Netherlands demonstrated that communication produces greater employee commitment. According to Van Vuuren, De Jong, and Seydel (2007),when an organization makes an attempt to provide sufficient information to its employees regarding the organization's vision, goals, and strategies, employees will feel that they are being valued, respected, and trusted by the organization. Furthermore, Van Vuuren et al (2007) advocated that communication helps sharpen employees' view of the things that the organization cherishes.…”
Section: Identification With Organizational Values and Goals As A Medmentioning
confidence: 99%
“…According to Van Vuuren, De Jong, and Seydel (2007),when an organization makes an attempt to provide sufficient information to its employees regarding the organization's vision, goals, and strategies, employees will feel that they are being valued, respected, and trusted by the organization. Furthermore, Van Vuuren et al (2007) advocated that communication helps sharpen employees' view of the things that the organization cherishes. As a result, employees' sense of identification with the organizational values will be enhanced.…”
Section: Identification With Organizational Values and Goals As A Medmentioning
confidence: 99%
“…Participation in decision-making, the adequacy of information and open communication were all positively related to organisational commitment (Putti, Aryee, & Phua, 1990;Vuuren, de Jong, & Seydel, 2007).…”
Section: Supervisor-subordinate Communication and Organisational Commmentioning
confidence: 99%
“…This support can guide employees in applying what they have learned in the training program after they return to work in the workplace. Secondly, communication is generally seen as administrators delivering the information about training content and procedures to employees, explaining the advantages of attending training programs and giving performance feedback to employees who have attended training programs (Chiaburu & Tekleab, 2005;Ismail & Bongogoh, 2007;Vuuren et al, 2007;Ismail et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…For example, the ability of administrators to adequately provide material and moral support, openly communicate the advantages and prospects of training programs, and properly implement voluntary and mandatory assignments may increase trainee motivations to apply what they have learned when returning to the workplace (Saks & Belcourt, 2006;Vuuren et al, 2007;Dawley et al, 2008). Extant studies about training administration have been conducted using different samples in different organizational contexts like perceptions of 207 trainees in an organization in United States , 193 trainees in the engineering group of a manufacturing organization in United States , 10 Korean HR practitioners in Korea (Lim, 2000), 184 employees belonging to 18 banks in Northern Taiwan (Tsai & Tai, 2002), 150 members of a large training and development society in Canada (Saks & Belcourt, 2006), 456 employees in telecommunication services in Dutch (Vuuren et al, 2007), and 346 employees from a manufacturing facility in US (Dawley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%